Study on the effect of Chinese herbal medicine stick beating therapy on the motor function and activity of daily living of stroke patients in convalescent period (药棒循经敲打对脑卒中恢复期患者肢体功能和日常生活活动能力影响的研究) - LI Chunhong (李春红) (中西医结合护理)
Objective To investigate the effects of Chinese herbal medicine stick beating therapy on limb function and activities of daily living in stroke patients in convalescent period. Methods A total of 104 stroke patients in convalescent period who admitted to the Acupuncture Ward of Hospital were randomly divided into treatment group (n=52) and control group (n=52). Patients in the control group received a comprehensive Traditional Chinese Medicine nursing plan including illness condition monitoring, medication care, rehabilitation exercise, diet guidance, emotion regulation and health education. On the basis of the treatment method carried out in the control group, the observation group was given the Chinese herbal medicine stick beating through the meridian. Barthel Index (BI) and Fugl-Meyer scale was used to evaluate the effect of interventions before the intervention, 14 days and 28 days after interventions. Results Scores of BI and Fugl-Meyer scale increased in both groups after intervention, and Scores of BI and Fugl-Meyer scale in the observation group were higher than those in the control group(P＜0. 05). The total effective rate was 96. 15%(50/52)in the observation group, which was higher than 76. 92%(40/52)in the control group (P＜0. 05). Conclusion The Chinese herbal medicine stick beating through the meridian can effectively improve the recovery of motor function and activities of daily living of patients in the convalescent period of stroke and improve the quality of their life. (目的 观察药棒循经敲打对脑卒中恢复期患者肢体功能及日常生活活动能力的影响。方法 将北京中医药大学附属护国寺中医医院针灸病房收治的104例脑卒中恢复期患者随机分为观察组(n=52)和对照组(n=52), 对照组患者参照脑卒中恢复期患者的中医护理方案(包括: 病情观察、给药护理、康复锻炼、饮食指导、情志护理及健康指导等)来进行护理; 观察组在对照组的基础上使用药棒循经敲打进行护理。分别在治疗前、治疗后第14天(2周)、治疗后第28天(4周)作为结点, 使用Fugl-Meyer量表和Barthel指数(BI)量表对患者进行评定。结果 干预4周后, 两组Fugl-Meyer量表和BI量表评分较干预上升(P＜0. 05), 且观察组Fugl-Meyer量表和BI量表总评分改善优于对照组, 差异有统计学意义(P＜0. 05)。观察组总有效率96. 15%(50/52), 高于对照组的76. 92%(40/52), 差异具有统计学意(P＜0. 05)。结论 药棒循经敲打可有效改善脑卒中恢复期患者的肢体功能和日常生活活动能力, 提高患者的生活质量。)